Evaluation of Kemuhammadiyahan Education Program Based on CIPP Method for Strengthening Muhammadiyah Kader - Subur, Subur; Hidayati, Istania Widayati (Jurnal Tarbiyatuna, 2020)
Muhammadiyah is a socio-religious organization that has the most charities organization in Indonesia and even in Southeast Asia. However, the lack of loyalty sense and totality in managing it causes a serious problem that hinders the development of the charity organisation in education, economy, health and society. For this reason, it is necessary to hold a tiered Kader and has a more comprehensive curriculum such as One Year Muhammadiyah Education program. The purpose of this study is to evaluate the implementation of One Year Muhammadiyah Education Program that had been implemented in Magelang and Temanggung. The method used in this research is CIPP (Context, Input, Process, Product) evaluation model. The respondents of this study are program graduates. This research is an evaluative study using a qualitative descriptive method. Collecting data using interview techniques and filling out questionnaire then analyzed by content analysis (content analysis). The results of the CIPP Evaluation study on Muhammadiyah Education can be used as recommendations for improving the implementation of the One Year Muhammadiyah Education Program in the next period.